2011
DOI: 10.1186/1472-6904-11-15
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal adverse effects of varenicline at maintenance dose: a meta-analysis

Abstract: BackgroundTobacco smoking remains the leading modifiable health hazard and varenicline is amongst the most popular pharmacological options for smoking cessation. The purpose of this study is to critically evaluate the extent of gastrointestinal adverse effects of varenicline when used at maintenance dose (1 mg twice a day) for smoking cessation.MethodsWe conducted a meta-analysis of randomised controlled trials published in PUBMED and EMBASE according to the PRISMA guidelines. Selected studies satisfied the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
0
18
0
1
Order By: Relevance
“…In 2007-2008, the EMA, the Medicines and Healthcare Products Regulatory Agency UK/ Committee for Medicinal Products for Human use (MHRA/ CHMP), and the FDA issued alerts regarding potential adverse events (e.g. signs of gastrointestinal side effects) [56], psychiatric disorders (e.g. anxiety, depressed mood, irrational behavior, drowsiness, abnormal dreams, sleepwalking, and occasional suicidal thoughts and behavior), and increased perception of colors.…”
Section: Vareniclinementioning
confidence: 99%
“…In 2007-2008, the EMA, the Medicines and Healthcare Products Regulatory Agency UK/ Committee for Medicinal Products for Human use (MHRA/ CHMP), and the FDA issued alerts regarding potential adverse events (e.g. signs of gastrointestinal side effects) [56], psychiatric disorders (e.g. anxiety, depressed mood, irrational behavior, drowsiness, abnormal dreams, sleepwalking, and occasional suicidal thoughts and behavior), and increased perception of colors.…”
Section: Vareniclinementioning
confidence: 99%
“…Essa substância química foi produzida em 1997 e aprovado pela FDA em 2006 (CAHILL;STEAD;LANCASTER, 2011). A vareniclina é comercializada pela Pfizer em mais de 90 países; nos Estados Unidos recebe o nome de Chantix®, e na União Europeia e no Brasil de Champix® (FAESSEL et al, 2010;LEUNG;PATAFIO;ROSSER, 2011;ERWIN;SLATON, 2014).…”
Section: -Introduçãounclassified
“…The US Food and Drug Administration (FDA) has issued a series of warnings, resulting from post-marketing reports of increased risk of suicidal behaviour or depression, serious adverse cardiac events and gastrointestinal complaints including a recently added warning highlighting a small increased risk of certain cardiovascular events in smokers with pre-existing cardiac conditions. A meta-analysis of adverse gastrointestinal events by Leung et al 27 showed an increased risk after treatment with varenicline. In a review of 10 trials, Tonstad et al 28 found no evidence of a link between varenicline and serious neuropsychiatric events.…”
Section: Safety Profile Of Vareniclinementioning
confidence: 99%
“…Leung et al 27 found an association between varenicline and an increased risk of gastrointestinal events. Tonstad et al 28 found no significant association between varenicline and serious neuropsychiatric events; however, an association has been suggested for those taking varenicline who are currently experiencing depression.…”
mentioning
confidence: 99%